Statistical evaluation of the incidence of hypertension among women - To'raboyeva Shaxnoza Xamidjon qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
Hypertension, or high blood pressure, is a significant public health concern globally, with women bearing a substantial burden of its incidence. This article aims to comprehensively explore the statistical landscape of hypertension among women, including prevalence rates, trends over time, and factors influencing its occurrence. Through a systematic review of existing literature, analysis of epidemiological data, and consideration of socio-demographic determinants, this study seeks to provide a nuanced understanding of hypertension incidence among women. By elucidating the statistical patterns and identifying key risk factors associated with hypertension in this demographic group, this research contributes to informing targeted interventions, healthcare policies, and preventive strategies aimed at reducing the prevalence and impact of hypertension on women's health outcomes.